Factors Influencing Shift of Livelihoods from the Agricultural to Non-Agricultural Sector in the Nickel Mining Area of Central Halmahera Regency - Mardiyani Sidayat; Sartika Syafi; Eka Kusuma Dewi; Mukhlis Mukhlis (Postgraduate, University of Mataram, 2026)
Indonesia has several leading sectors that support the national economy, one of which is the agricultural sector. However, over time, there has been a significant shift of labor from the agricultural sector to non-agricultural sectors. This large-scale labor migration has implications for the development and sustainability of the agricultural sector. In the context of North Maluku, the mining sector has emerged as a leading economic sector, particularly in regions such as Central Halmahera. The presence of the mining industry has contributed to changes in local livelihood structures, marked by a shift of labor from the agricultural sector to non agricultural sectors that develop as multiplier effects of mining activities. This study aims to identify the factors influencing the transition of livelihoods from the agricultural sector to non-agricultural sectors in mining areas surrounding Central Halmahera. The research employs descriptive analysis and multiple linear regression methods. The independent variables examined include the reduction of agricultural land (X1), income uncertainty in the agricultural sector (X2), job opportunities in non-agricultural sectors (X3), and income stability in non-agricultural sectors (X4). The results show that the partial regression analysis (t-test) indicate that the reduction of agricultural land (X1) and employment opportunities in the non-agricultural sector (X3) have a statistically significant influence on livelihood shifting (Y). In contrast, uncertainty in the agricultural sector (X2) and income stability in non-agricultural sectors (X4) do not demonstrate a statistically significant influence on livelihood shifting (Y). Furthermore, the results of the simultaneous analysis indicate that these variables collectively have a significant influence on the shift in livelihoods from the agricultural sector to non-agricultural sectors